Penerapan PHBS Melalui Progam Senam Dan Bawa Bekal Sendiri Bagi Siswa SDN Kunir Lor 3 - Imam Ali Syibro Mulis; Ahmad Sulaiman (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
The realization of a healthy school starts with students' habits of implementing a clean and healthy PHBS lifestyle, health is the main foundation in supporting an optimal learning process, in implementing clean and healthy living behavior and also one of the main factors driving good and correct PHBS for students is teacher, improving a person's quality of life is those who pay attention to the condition of their body, by diligently exercising, eating healthy food, and getting enough sleep, strategies for implementing a clean and healthy lifestyle at SDN Kunir Lor 3, and how this can contribute positively to health and student immunity, unhealthy student lifestyles such as students who usually eat instant food, junk food and unclean student habits. Seeing the situation of students who are unhealthy and lack immunity, we have the initiative to create a healthy lifestyle work program for students by means of exercise and bring supplies. Through direct analysis surveys before and after implementing the exercise program and bringing provisions, a decrease in the level of boredom and laziness among students was seen. The success of the gymnastics and carrying provisions program at SDN Kunir Lor 3 has been a positive experience. This positive experience has sparked interest in the integration of gymnastics and carrying provisions into educators' routines as a method for improving the quality of education.